Robotim: aprendizado lúdico e avaliação de desempenho em um jogo multidisciplinar para a educação - Oliveira, Lucas Rios Escóssia de (2023)
Traditional teaching can be enriched with more playful and engaging approaches. This research aims to explore the creation of a multidisciplinary, competitive, and enjoyable educational game spanning various subjects to assist in the knowledge construction of elementary school students. Thus, Robotim was born, highlighting the importance, attractiveness, and effectiveness of the game as a learning tool. Additionally, a platform has been developed to enable teachers to track students’ performance, transforming a fun educational game into a powerful tool that aids teachers in measuring their students’ learning progress. Experiments applying Robotim were conducted in elementary schools. The tests revealed tangible results, showcasing its excellent reception by both students and teachers. The game achieved an excellent quality rating according to the MEEGA+ quality model. Furthermore, the data platform proved to be a valuable tool for adapting teaching to individual student needs. It becomes evident that the interaction between the educational game and the data platform not only benefits students but also teachers.